METHODOLOGICAL INDIVIDUALISM AND HUMAN MODEL IN ORTHODOX ECONOMIC THEORY (Globalization and Business, 2018)
Today it is widely recognized that the economic development is largely determined by the decision taken by economic agents.Modern economic science does not provide an undeniable and perfect definition of economic agents’economic behavior and a universally recognized and having no alternative model of human behavior is not yet formulated in the economic theory.Scientists proceed from the different methodological approaches and use various characteristics for the development perceptions regarding human behavior.Despite a large number of scientific schools, directions, and divisions of modern economic theory, there is a dominant model of human behavior which represents a specific orientation and comparable model for other economic schools this is the model of Homo Economicus that arose within the classical economic theory and was developed by the neoclassical economic school. This model is considered to be one of the founding dogmas of the modern Mainstream Economics in which the classical economic theory has reached the highest level of formalization.The given article considers the peculiarities and interconnections of orthodox economic theory and Mainstream Economics and mentions that along of evolution of their interrelations the optimization behavior, the principles of minimizing expenses and maximize of a profit still remain to be a general methodological approach.The modern economic mainstream is based on the fundamental postulate such as methodological individualism that is most widely used an analytical method in modern economic science. According to methodological individualism, the human behavior is the main indicator of the nature of economic phenomenaThe traditional microeconomic orthodox theory considers human beings as independent, associative, selfish, and rational species, which have stable and exogenous preferences and in every particular moment have full information about the current situation and use the information in order to satisfy own egoistic interests with a purpose to maximize a benefit.To define the model of economic men the acronym REMM (or «Resourceful, Evaluative, Maximizing Man») proposed by Karl Brunner and William H.Meckling is used. Based on the development of the acronym REMM the acronym RREEMM(or„Resourceful, Restricted, Expecting, Evaluating, Maximizing Man”)was developed. Other models of human behavior were developed by a sociologist Siegwart Michael Lindenberg. He distinguishes two types of human behavior and presents them by acronyms SRSM (or “Socialized,Role-Playing, Sanctioned Man”)and OSAM(or“Оpinionated,Sensitive, Acting Man”).The human behavior model is a fundamental and systematic element for any direction of the modern economic theory. Every economic school develops its own model of human behavior that best illustrates this school as a theoretical system.